ORIGIN OF DYSLALIA AND WAYS OF ITS ELIMINATION - Kabirova Zarnigor Rakhmonjonovna; Havodullayev Murodjon; Ibrokhimova Sarvinoz Anvarjonovna (American Journals, 2023)
This article describes the causes of dyslalia, diagnosis of dyslalia and step-by-step treatment methods, methods of eliminating dyslalia, and conclusions and suggestions on the topic. Dyslalia is a violation of sound pronunciation during the preserved innervation of the normal auditory and speech apparatus.
Keywords: Chuchukli, rotatism, lambdatism, sigmatism, surgery, differential, mechanism, functional, prognathia, pricus, articulation, kinesthetic analysis, realization, imitation, Yugancha,